A tradução de expressões idiomáticas de baixa dedutibilidade metafórica: contribuições aos estudos fraseológicos bilíngues - Valença, Eloísa Moriel [UNESP] (2016)
Taking into account the metaphorical variations of idiomatic expressions as well as the notion of correspondence proposed by the translation theories, this study aims to examine Italian Idiomatic Expressions of Metaphorical Low-Deductible (EIBDM), from the point of view of the Brazilian learner / translator, whose search for translational correspondences is a challenge. By EIBDM, we mean those combinatorial expressions in foreign language which presents, in its constitution, cultural metaphors difficult to understand in the target language because it contains historical, geographical, religious, mythological, weather (temporal) or simply linguistic elements, explicit or implicit, that are typical or significant only in the source language or in the native language (in our case, the Italian). It is a multidisciplinary research, guided by the theoretical frameworks regarding Lexicography and Phraseography (PORTO DAPENA, 2002; OLIMPIO DE OLIVEIRA E SILVA, 2007), Phraseology, Idiomatic Expressions and Culturemes (ZULUAGA, 1997; ORTÍZ ALVAREZ, 1997, 2000; CORPAS PASTOR, 1996; XATARA, 1995, 1998; PAMIES BERTRÁN 2007, 2008; MOLINA MARTINEZ, 2001), Metaphor and Metonymy (LAKOFF AND JOHNSON, 2002; KÖVECSES 2002, 2005, 2010) as well as Translation Studies (FELBER, 1984; BAKER, 1992) to support this research. The corpus of this investigation was selected from special dictionaries of IEs; the methodology was based on the use of the web as a corpus and on the establishment of the frequency of occurrence of Italian IEs.72 EIBDM were selected and classified typologically. Then an analysis of their metaphors was carried out, translational correspondences were proposed and a discussion of the underlying cultural aspects were presented. Furthermore, a dictionary model of this phraseological units was designed, for learners, teachers and translators of the Italian language. On that basis, this research sought to outline the path to be followed and the challenges to be faced in translating these phraseologisms, in order to provide theoretical and practical background to phraseological bilingual studies.